Socioeconomic Variation in Emotional, Cognitive, and Behavioural Engagement with the Climate Crisis in England: Perspectives for Education - Rachael C. Edwards; Joy Perry; Nicola Walshe (Behavioral Sciences)
Issues of economic inequality are inextricably linked to the present climate and environmental crisis, with disadvantaged groups facing disproportionate impacts. This paper explores the intersection of socioeconomic status (SES) and degrees of emotional, cognitive, and behavioural engagement with the climate crisis, as well as equity in the provision of climate change and sustainability education (CCSE). We surveyed over 2000 students (ages 11–14) in England, comparing responses between students with the most (n = 599) and fewest (n = 389) books at home (as a proxy for SES). Students from lower socioeconomic backgrounds were significantly less worried about a climate-altered future, had lower levels of knowledge about climate change, and were less likely to undertake a range of pro-environmental behaviours. Our findings also emphasise the critical role of the school environment in promoting engagement with the climate crisis and the need to improve provision of CCSE for disadvantaged groups. Further, they reveal severe socioeconomic inequalities in the perceived experiences of CCSE and participation in climate and sustainability action, which was observed even when these activities were made available. This suggests that school systems must consider other possible explanations for whether disadvantaged children and young people engage with these issues beyond their opportunity to do so.